RESEARCH ON THE INFLUENCE OF DESTABILIZING FACTORS ON MEASURING DISTANCES ON A STANDARD CALIBRATION BASELINE OF THE 2ND CATEGORY - Rii, І.; Bochko, О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
The research on the influence of environment destabilizing factors on the process of measuring standard calibration baseline distances of the geodetic testing field is considered. The authors have carried out an investigation of meteorological conditions at the geodetic testing field of Lviv National Environmental University. The significance of destabilizing factors for the total measurement error during the metrological control of the distance measuring part of total station theodolites on the standard calibration baseline of the 2nd category of Lviv National Environmental University is checked. The research results can be used to estimate the value of the random component error during metrological control of distance measuring devices in the geodetic testing field. One of the most effective methods of comprehensive research of the specified measuring technique is its calibration on stationary sample baselines. The metrological certification of rangefinder telemeters is based on regulatory documents, according to which the metrological verification of devices is carried out on the model linear baselines of the 2nd category, the accuracy of which is 1.5·10-6. The basic linear geodetic testing field is a standard for ensuring the unity of linear measurements in geodetic networks, the transfer of a unit of physical value of length – a meter from the standard to working devices: light rangefinder telemeters, electronic total station theodolites and other geodetic devices for measuring distances. Such testing field can also be used to test satellite communication devices. Considering the increasing accuracy of modern geodetic instruments, it is necessary to ensure that the accuracy of standard calibration linear baselines is at least three times better than the one of the measuring equipment being tested. For the calibration of geodetic instruments, one needs to be aware of high accuracy of the distance between the baseline points and track their possible changes over time due to the weather and other conditions. Therefore, the issue of researching stability of the centers of points of the model baselines, which perform the metrological function of preserving a unit of distance in the area during a certain time, is of great importance. The issue of the influence of destabilizing factors of environment on the process of measuring geodetic baseline distances is being considered. The research results can be applied to estimate the magnitude of the random component error during metrological control of distance measuring devices on a sample baseline.